Forecasting and Inventory Management on Room Occupancy and Housekeeping of the PCED Hospital - Reyes, Fernando G.; Cuyugan, Josephine Regina B. (Diliman, Quezon City College of Engineering, 1991)
The study on Forecasting and Inventory Management on Room Occupancy of the PCED Hostel was conducted to enable the students to apply their knowledge on forecasting, resource management, scheduling, and control to a real life situation. The study's primary aim was to formulate a forecasting model for the room occupancy of the PCED Hostel. The student researchers also investigated the adequacy and effectiveness of the Hostel's cleaning materials inventory system, and its linen inventory tracking and monitoring system. To fulfill the objectives of our research, information on past occupancy and room use, current inventory (acquisition), and linen monitoring system, concerned departments were requested for their cooperation. Research on the various forecasting models was conducted in order to choose an adequate technique. Studies were performed on methods for variable correlation, and inventory management and monitoring. All appropriate techniques or methods were then applied to the data to obtain a feasible conclusion.
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: PCED Hospital; Hospitals; Production engineering